2019
DOI: 10.1021/acs.iecr.8b05465
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Matrix Effects in Laboratory Studies of Catalytic Ozonation Processes

Abstract: A systematic study investigating the effects of water matrices on heterogeneous catalytic ozonation processes was conducted in a semibatch reactor at initial pH 7.00 ± 0.20. Specifically, three matrices commonly used in laboratory studies were tested: deionized (DI) water, phosphate buffered solution, and tetra-borate buffered solution. Three metal oxide catalysts on SiO2 support, CuO/SiO2, Fe2O3/SiO2, and MnO2/SiO2 (all ∼4.5% metal loading), were synthesized and used as representative solid catalysts. Oxalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The variation in the contributions of radical and nonradical mediated processes with the nature and concentration of target organic as well as the catalyst dosage may contribute to the discrepancies in the mechanisms of the HCO process reported in various earlier studies. 10,16,61,62 The significant variability in controlling processes as a function of reaction conditions is particularly evident for the degradation of HCOO − in the presence of CuO where surface reaction control is evident at higher catalyst loadings and low HCOO − concentrations while degradation reactions in solution dominate at higher HCOO − concentrations.…”
Section: Environmentalmentioning
confidence: 99%
“…The variation in the contributions of radical and nonradical mediated processes with the nature and concentration of target organic as well as the catalyst dosage may contribute to the discrepancies in the mechanisms of the HCO process reported in various earlier studies. 10,16,61,62 The significant variability in controlling processes as a function of reaction conditions is particularly evident for the degradation of HCOO − in the presence of CuO where surface reaction control is evident at higher catalyst loadings and low HCOO − concentrations while degradation reactions in solution dominate at higher HCOO − concentrations.…”
Section: Environmentalmentioning
confidence: 99%
“…This may be explained by the fact that 0.5 wt % AgMnFe 2 O 4 prepared in our study has a pH pzc of 6.98 (Table S1). Catalysts usually have the maximum ozone decomposition capability when surface hydroxyl groups are mostly zero-charged, ,, and consequently the ATZ removal efficiency was increased. As the main reactive oxidant, a higher O 3 dose led to a faster ATZ removal (Figure S9B).…”
Section: Resultsmentioning
confidence: 99%
“…To start an experiment, catalysts, atrazine, and 150 mL of ozone solution were added into the reactor, and the mixture was continuously stirred at 500 rpm at room temperature (22 ± 2 °C). Unless otherwise noted, experiments were conducted in unbuffered deionized (DI) water to eliminate the interfering effects of other inorganic ions . The initial pH was adjusted to a desired value using NaOH, and the pH evolution during the experiments was monitored.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…However, opposite conclusions were derived in another study. 290 The discrepancies in these studies might be explained by the combined effects of ionic strength, which inuences the solubility and mass transfer of O 3 , the reaction rates of ROS, and the interactions of O 3 and organics on catalyst surface. It was reported that the solubility and mass transfer of O 3 decrease as ionic strength grows, especially when Cl À , CO 3 2À and PO 4 3À are present, while SO 4…”
Section: Inorganic Anionsmentioning
confidence: 99%
“…299,300 Notably, the induced alkalinity with the presence of CO 3 2À and PO 4 3À as basic anions would promote the base activation of O 3 and affect the surface charge of the catalyst. 287,290 Therefore, special attention should be paid to the variation in solution pH with the presence of basic anions. In the most of current studies, individual effects of inorganic anions on the activation of O 3 have been well evaluated.…”
Section: àmentioning
confidence: 99%